Improving Students’ Role in Group Work Through Problem-Based Learning in English Language Learning for Grade X at SMA Negeri 3 Bogor - Rahmawati, Yurike Resty; Mawaddah, Syarifah; Antari, Ima Yosi; Herawati, Atti (Indonesian Journal Publisher, 2025)
The current classroom action research aims to enhance the active participation of the students in group tasks through the application of Problem-Based Learning (PBL) approaches in the context of English language learning for Grade X students of SMA Negeri 3 Bogor. This study addresses the problem of the lack of student participation and contribution in group tasks, which has negatively affected the effectiveness of collective learning results. The research was conducted in two cycles, with planning, action, observation, and reflection in each cycle. The data were obtained from observation, students’ test scores to assess their grammar mastery, and from reflective journals to gain insight into their learning experiences and engagement with the instructional methods. The results showed that PBL approach, particularly after integrating game-based learning elements in the second cycle, was effective in increasing students’ engagement during group work by encouraging better communication, cooperation, and responsibility among members. Students became more confident in sharing ideas, showed greater enthusiasm, and demonstrated improved understanding of gerunds and to-infinitives, which was also reflected in the increase of their average test scores from 41,08 to 66,27. This indicates that when PBL is applied in a structured and interactive way, it can significantly enhance student participation and improve grammar learning outcomes.